Occurrence of Oncicola sp. (Acanthocephala) in Atelocynus microtis (Canidae) from the Manu Biosphere Reserve, Madre de Dios, Peru - Tantaleán, Manuel (2011)
During a large survey of mammals and their parasites, which took place in the Manu Biosphere Reserve, Madre de Dios, Peru, two specimens of Atelocynus microtis, short eared dog, were captured from which some acanthocephalan specimens were collected. Albeit it was not possible to identify them up to species level basically due to their immature condition, all of them were diagnosed as members of the genus Oncicola Travassos, 1916.